PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN SMARTBOX TERHADAP HASIL BELAJAR PADA MATERI PECAHAN DI KELAS V SDN 060874 MEDAN PERJUANGAN - Anggita Siva Liana Nst; Wildansyah Lubis; Elvi Mailani; Sri Mustika Aulia; Syahrial (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using Smartbox learning media on students' Mathematics learning outcomes on fraction material in class V SDN 060874 Medan Perjuangan. The research method used is quantitative with a quasi- experimental design using a nonequivalent control group design. The population in this study were all students of class V SDN 060874 Medan Perjuangan. The sample in this study consisted of two classes, namely class V-B consisting of 20 students as experimental class 1 and class V-A consisting of 20 students as experimental class 2. Data collection techniques were carried out through tests, observations, and documentation. The instruments in this study used tests in the form of pretests and posttests that had gone through a series of tests, namely validity tests, reliability tests, difficulty level tests, discriminatory power tests and question distractors to ensure the quality of the questions. The data analysis technique was carried out through several stages, namely, normality tests, homogeneity tests and hypothesis tests. The results of the analysis showed that the average posttest score of experimental class 1 was 84.3 with a learning completion of 95%, while experimental class 2 had an average of 78.3 with a completion of 80%. The results of the hypothesis test calculation using the Independent Sample T-Test showed a significance value of 0.043 <0.05, with the acquisition of t-count (2.091)> t-table (2.024) so that it states that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Thus, it can be concluded that there is a significant effect of the use of Smartbox learning media on learning outcomes in fraction material in class V SDN 060874 Medan Perjuangan.